PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO A LA PARROQUIA DE VILCABAMBA DEL CANTÓN Y PROVINCIA DE LOJA - Tillaguango Guzmán, Elsa Marcela (2016)
To develop the thesis called "PROJECT FEASIBILITY FOR THE CREATION OF A SAVINGS BANK TO PARISH Vilcabamba Loja province," to give compliance with the objectives proposed in the thesis the market study was conducted, using a survey to have real information for the development and implementation of savings reaching 98% who do agree with the creation of the same, plus the unsatisfied demand is 768 and 1287 year 1 was calculated and 5 respectively which showed that if there are partners for Savings ie the project has market acceptance. In technical survey, capacity, location and distribution of the savings that will be for their good performance with efficient service, which will be located in the parish of Vilcabamba between the streets Juan Montalvo and sucre near the longhouse it was known the parish. The legal / administrative study was developed to establish the type of enterprise that is a savings and ensure smooth functioning of it. In others, the administrative study the administrative and legal organization of the box showed. For economic / financial study investment that will take the project to its implementation both fixed, deferred assets, and working capital for a total of $ 6430.54 initial investment outlined above. 5 Taking a profit of 3.168,29 considering that the income is interest earned 13% Internal rate of return is 71.07% compared to the opportunity cost of capital is 9.41% one can say that the project is feasible because the IRR is greater than the opportunity cost. Capital recovery period, the recovery of invested capital is 1 year, 5 months and 18 days, a period in which the housing recover the investment. Cost sensitivity analysis resists an increase of 13.67% and with respect to income may decrease by 9.79% which disclosed that the project is viable. Methods such as scientific, deductive, inductive, analytical and synthetic techniques direct observation, bibliography, sample and survey was used for carrying out the thesis, which allowed analyze and interpret the results for the efficient development work thesis. With all the information obtained in steps work was concluded that if the project is feasible and the creation of the savings in the parish of Vilcabamba is recommended.